New insight on the photofragmentation of CH2I2. (August 2015) - Casavola, A R; Cartoni, A; Bolognesi, P; Borocci, S; Avaldi, L
Synopsis: An experimental and theoretical investigation of the VUV photofragmentation of CH2 I2 molecule is reported. The work focuses on the I-loss channel. The experimental results demonstrate that at energies lower than 12 eV diiodomethane radical cation dissociates only into the CH2 I + ion and an I atom while the theoretical calculationsshow that isomerisation of [CH2 I2 ] + into iso-diiodomethane [CH2 I-I] + intermediates can occur before the loss ofiodine atom.